Tokenism in Manandhars: An Ethnolinguistic Study - Shrestha, Omkareshwor (Gipan, 2017)
This is an ethnolinguistic study of Manandhars of Kathmandu. Manadhars ‘the oil pressers’ locally called them Saemi, are the chunk of Newar society in Nepal. They are scattered in seven major oil pressing mills in Kathmandu, Bhaktapur, Kabhre, hence called them Nhaesah saemi (the oil pressers of seven mills). Besides, they play the traditional musical instruments. They are identified or differentiated with totems, which are based on their profession, physique, nature, locality, which is called Kunam or Binamin short for kulnam (clan name) and bishesnam (special name). Among the seven mills, only three mills (Pakopukhudyami, Nhusahmi, and Casandomi) practice totemism.